Biomass combustion: Environmental impact of various precombustion processes. (10th July 2020) - Tao, Junyu; Hou, Li'an; Li, Jian; Yan, Beibei; Chen, Guanyi; Cheng, Zhanjun; Lin, Fawei; Ma, Wenchao; Crittenden, John C.
Abstract: Mainstream biomass precombustion processes include anaerobic digestion (AD), gasification (GS), fast pyrolysis (FP), and hydrothermal liquefaction (HTL). Precombustion processes determine the forms of biomass-derived fuels, the energy production per mass of biomass and the creation of pollutants; consequently, it is important to determine the impacts of precombustion processes on these metrics. Current environmental evaluation methods have limitations when comparing various technologies. Accordingly, we proposed an index for the environmental impact of biomass preprocessing (EIBP), which includes carbon footprint reduction, pollutant impacts from byproducts and pollutant impacts from residuals. A higher EIBP value implies a worse environmental impact. We evaluated the EIBPs for a variety of processes and feedstocks. Technical levels of these processes were quantified by carbon conversion, which is equal to the sum of the carbon mass in the target products and byproducts divided by the total carbon mass in the feedstock. By adjusting the carbon conversion, we inferred the environmental potentials of these processes. We found that AD had the lowest EIBP and EIBP lower bound, the latter of which refers to the theoretically lowest EIBP under idealized conditions. This result implies that AD is likely to maintain its environmental impact advantage for a decade. Although the newly developed HTL technology had the highest EIBP for almost all feedstocks, it had an extremely high environmental impact improvement potential. The correlation analysis between the energy conversion efficiency and the EIBP showed that they do not necessarily have strong correlations, suggesting that environmental impact should be considered separately when optimizing biomass precombustion processes. Highlights: An environmental evaluation method of biomass precombustion processes is proposed. The method solves drawbacks of life cycle assessment method for comparative study. The method reveals environmental impact upper bound of these processes. Anaerobic digestion shows better environmental impact and enhancement potential. Energy and environment performances show weak correlation for these processes.